2011
DOI: 10.3727/096368910x539092
|View full text |Cite
|
Sign up to set email alerts
|

Tumorigenic Development of Induced Pluripotent Stem Cells in Ischemic Mouse Brain

Abstract: Induced pluripotent stem (iPS) cells may provide cures for various neurological diseases. However, undifferentiated iPS cells have high tumorigenicity, and evaluation of the cells fates, especially in pathologic condition model, is needed. In this study, we demonstrated the effect of ischemic condition to undifferentiated iPS cells fates in a mouse model of transient middle cerebral artery occlusion (MCAO). Undifferentiated iPS cells were characterized with immunofluorescent staining. The iPS cells (5 × 10 5 )… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
64
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(66 citation statements)
references
References 31 publications
(39 reference statements)
1
64
0
Order By: Relevance
“…5 However, the risk of tumorigenicity is a major obstacle hindering clinical application of iPS cells. [32][33][34] Zhang et al reported that intramyocardial transplantation of undifferentiated rat iPS cells causes tumorigenesis in the heart. 35 Previous studies demonstrated that the residual undifferentiated iPSD can form teratomas after cell transplantation, and Fu et al 36 reported that even extended periods of cell differentiation do not fully eliminate residual undifferentiated iPS cells.…”
Section: Discussionmentioning
confidence: 99%
“…5 However, the risk of tumorigenicity is a major obstacle hindering clinical application of iPS cells. [32][33][34] Zhang et al reported that intramyocardial transplantation of undifferentiated rat iPS cells causes tumorigenesis in the heart. 35 Previous studies demonstrated that the residual undifferentiated iPSD can form teratomas after cell transplantation, and Fu et al 36 reported that even extended periods of cell differentiation do not fully eliminate residual undifferentiated iPS cells.…”
Section: Discussionmentioning
confidence: 99%
“…There are significant similarities between cancer cells and iPSCs, which include certain molecular properties, the ability to self-renew, rapid unlimited proliferation, high telomerase activity, expression profiles, and epigenetic signatures (78). As one of the criteria for pluripotency, iPSCs are known to form teratomas in immunocompromised recipients after subcutaneous, intratesticular, or intramuscular injection (79,80). The teratoma-forming capability of the differentiated iPSCs derived from different adult tissues varied substantially and correlated with the number of residual pluripotent cells (81).…”
Section: Challenges To Be Addressed In Preclinical Studiesmentioning
confidence: 99%
“…iPSCs can be generated by transduction of defined transcription factors from adult somatic cells through reprogramming (4) and have been differentiated in vitro into the early neural stem cell stage or the neural lineage, including neurons and glial cells (5)(6)(7). More recently, iPSCs have been applied to a variety of nervous system disease models, including Parkinson disease (8), spinal cord injury (9,10), and stroke (11)(12)(13)(14), and were found to improve neural function (11,13,15). However, to better understand the in vivo behavior and efficacy of iPSCs, a noninvasive, sensitive, and clinically applicable approach for tracking the transplanted iPSCs and monitoring the therapeutic response in living subjects is warranted.…”
mentioning
confidence: 99%